1999
DOI: 10.1016/s0014-5793(99)01011-x
|View full text |Cite
|
Sign up to set email alerts
|

Improved germination under osmotic stress of tobacco plants overexpressing a cell wall peroxidase

Abstract: The cell wall is a fundamental component in the response of plants to environmental changes. To directly assess the role of the cell wall we have increased the expression and activity of a cell wall associated peroxidase (TPX2), an enzyme involved in modifying cell wall architecture. Overexpression of TPX2 had no effect on wild-type development, but greatly increased the germination rate under high salt or osmotic stress. Differential scanning calorimetry showed that transgenic seeds were able to retain more w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
50
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(54 citation statements)
references
References 26 publications
3
50
0
1
Order By: Relevance
“…This peroxidase shows high homology to soybean seed peroxidase (Gijzen et al 1999). Furthermore, over-expression of peroxidase TPX2 in transgenic tobacco plants was found to result in improved germination under osmotic stress (Amaya et al 1999). We also observed that ASR1 over-expression resulted in an increased expression of seed imbibition protein homologue ( Fig.…”
supporting
confidence: 60%
“…This peroxidase shows high homology to soybean seed peroxidase (Gijzen et al 1999). Furthermore, over-expression of peroxidase TPX2 in transgenic tobacco plants was found to result in improved germination under osmotic stress (Amaya et al 1999). We also observed that ASR1 over-expression resulted in an increased expression of seed imbibition protein homologue ( Fig.…”
supporting
confidence: 60%
“…Peroxidases are involved in many important plant processes, such as the crosslinking of molecules to constituent polymers of the cell wall, auxin oxidation, and responses to biotic and abiotic stresses (Fukuda, 1996;Kristensen et al, 1997;Amaya et al, 1999). The most extensively studied plant peroxidases are those of horseradish (Veitch and Smith, 2001), Armoracia rusticana, which include the ®rst for which the amino acid sequence was determined (Welinder, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…Many attempts have been made to confer resistance to pathogens and increase tolerance to abiotic stress to plants of agronomic interest. One of the most widely used strategies is to overexpress plant genes that are induced after biotic or abiotic stresses, such as chitinases and glucanases (Alexander et al, 1993;Hong and Hwang, 2006), vacuole and plasma membrane sodium transporters (Apse and Blumwald, 2002;Shi et al, 2003), mitogen-activated protein kinases (Piao et al, 2001;Zhang and Liu, 2001;Xiong and Yang, 2003), transcription factors (Park et al, 2001), peroxidases (Amaya et al, 1999), disease-related R genes, and ferritins (Deak et al, 1999). Alternatively or complementarily, efforts have been made to reinforce the plant array of responsive genes by introducing heterologous genes of well-known antipathogenic effect belonging to other phylla (Lorito et al, 1998;Bolar et al, 2001;Garg et al, 2002;Schutzendubel and Polle, 2002;Kunze et al, 2004).…”
mentioning
confidence: 99%